2013
DOI: 10.1038/srep01743
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating room-temperature Suzuki coupling reaction with light: Mott-Schottky photocatalyst for C-C-coupling

Abstract: The Suzuki coupling reaction is one of the most practiced classes of catalytic C-C bond formation. The development of new means of activating molecules and bonds over old catalysts for C-C bond formation is a fundamental objective for chemists. Here, we report the room-temperature C-C bond formation over heterogeneous Pd catalysts by light-mediated catalyst activation. We employ stimulated electron transfer at the metal-semiconductor interface from optically active mesoporous carbon nitride nanorods to Pd nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(144 citation statements)
references
References 39 publications
2
135
0
2
Order By: Relevance
“…Li et al reported a Mott−Schottky-type photocatalyst, C 3 N 4 -supported Pd nanoparticles, for Suzuki−Miyaura coupling reactions under UV irradiation. 11,12 In the Pd/C 3 N 4 catalyst, Pd nanoparticles obtain photogenerated electrons via the Mott−Schottky heterojunction between Pd and C 3 N 4 . Cubic silicon carbide (β-SiC) possesses a suitable band gap (∼2.4 eV) and can absorb visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported a Mott−Schottky-type photocatalyst, C 3 N 4 -supported Pd nanoparticles, for Suzuki−Miyaura coupling reactions under UV irradiation. 11,12 In the Pd/C 3 N 4 catalyst, Pd nanoparticles obtain photogenerated electrons via the Mott−Schottky heterojunction between Pd and C 3 N 4 . Cubic silicon carbide (β-SiC) possesses a suitable band gap (∼2.4 eV) and can absorb visible light.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd-catalysed Suzuki-Miyaura coupling reaction has become a central tool for the construction of C-C bonds, widely used to synthesize natural products, non-natural products, and other bioactive compounds, as well as some advanced materials [1][2][3][4]. Traditionally, the C-C coupling reactions are carried out in organic solvents such as tetrahydrofuran and diethyl ether in the presence of Pd(II) or Pd(0) complexes having organic ligands at higher temperatures [5][6][7]. However, there are some glaring disadvantages in this case.…”
Section: Introductionmentioning
confidence: 99%
“…Basing on the mechanism of activation of homogeneous Pd-containing catalysts which depend on the electron-enrichment caused by the introduction of special ligands, Li et al [181] were interested in increasing the activity of heterogeneous Pd nanoparticle-based catalysts by increasing their electron density via support effects. The authors employed the stimulated electron transfer at the metal-semiconductor interface from optically active mesoporous carbon nitride (g-C 3 N 4 ) nanorods to Pd nanoparticles.…”
Section: Scheme 58 Smc Under Light Irradiationmentioning
confidence: 99%